The Morphometric Analysis of the Patella from the Male Cadaveric Native Knees of the Ethnic Igbos of Southeast Nigeria and Its Implications in Total Knee Replacement - Katchy, Amechi Uchenna; Agu, Augustine Uche; Ikele, Ikenna Theophilus; Ikele, Chioma Nneka; Ugwu, Augustus Uchenna (Nigerian Journal of Orthopaedics and Trauma, 2020)
Background: In forensic study, the importance of the patellar morphometry for human identification has been widely accepted, and it also plays a role in the biomechanics of the knee. Aim: The aim of this study is to analyse the morphometric parameters of patella from the cadaver of the Igbo population of South‑east Nigeria. Materials and Methods: Parameters from 60 patellae from 30 male cadavers at the museum of the Department of Anatomy University of Nigeria were measured using the Vernier calipers. Results: The determined values of the parameters of the cadaveric knees in centimetres are as follows: PH: M =4.6, SD = 0.47, PW: M =4.69, SD = 0.29, PT: M =2.66, SD = 0.15, PLH: M = 6.67, SD = 0.67, PLW: M = 2.86, SD = 0.27, WMAF: M = 2.55, SD = 0.18, WLAF: M =2.77, SD = 0.18. The results of the independent sample t‑tests indicated that there were no statistically significant differences in the mean values of the parameters of interest between the left and right patella. The result of the Pearson correlations between PH and other parameters indicated there was a very strong positive significant correlation with PW: (r[60] =0.924, P < 0.01), the PW had a strong positive significant correlation with PT (r[60] = 701, P < 0.001), WMAF (r[60] = 763, P < 0.01), and WLAF (r[60] = 700, P < 0.001). The PT had a weak significant positive correlation with PLW (r[60] = 0.338, P = 0.008) and WMAF (r[60] =0.479, P < 0.001). The PLW was weakly significantly positive correlated with WMAF (r[60] = 0.486, P < 0.001) and WLAF (r[60] = 0.403, P = 0.001). The WLAF was strongly significantly positive correlated with WMAF (r[60] = 0.975, P = 0.001). The PH among the Igbo population (M = 4.61, SD = 4.7) was significantly higher than that of Koreans (t[59] = 2.543, P = 0.014) with a small effect size (Cohen’s d = 0.33). The PT among the Igbo population (M = 2.66, SD = 0.15) was significantly higher than Korea (t[59] = 22.278, P < 0.01) with a large effect size (Cohen’s d = 2.88). Conclusion: This study has established that there are differences with the parameters of interest Igbo ethnic group with that of other populations of interest. The determined values will serve as a guide in the selection of patella component sizes among the studied population.